2018
DOI: 10.3390/nano8090729
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Nano-Carbon Reinforced Titanium Matrix/Hydroxyapatite Biocomposites Prepared by Spark Plasma Sintering

Abstract: Nano-carbon reinforced titanium matrix/hydroxyapatite (HA) biocomposites were successfully prepared by spark plasma sintering (SPS). The microstructure, mechanical properties, biocompatibility, and the relationship between microstructure and properties of biocomposites were systematically investigated. Results showed there are some new phases in sintered composites, such as β-Ti, TiO3, ZrO2, etc. Moreover, a small amount of Ti17P10, CaTiO3, Ca3(PO4)2 were also detected. The reaction that may occur during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…That means, when Ag content in coatings reach 0.58 wt% (Sr/Ag0.17 group), both short‐term and long‐term antibacterial properties can be obtained. Some previous studies also explored the long‐term antibacterial properties of titanium coatings, 4,32 but their results were either achieved by a duplex technique or based on several change of immersion solution. The MAO technique used in this study is more simple and PBS for specimen immersion was changed every day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That means, when Ag content in coatings reach 0.58 wt% (Sr/Ag0.17 group), both short‐term and long‐term antibacterial properties can be obtained. Some previous studies also explored the long‐term antibacterial properties of titanium coatings, 4,32 but their results were either achieved by a duplex technique or based on several change of immersion solution. The MAO technique used in this study is more simple and PBS for specimen immersion was changed every day.…”
Section: Discussionmentioning
confidence: 99%
“…Ag is the strongest element against microbes 3,4,6,14,23,24,26 and it can kill bacteria either in its ion form or by a mechanism of contact‐killing 28,30,32 . Direct contact of Ag with bacteria will cause destruction of cell wall and plasma membrane, leading to leakage of intracellular substances and eventually bacteria lysis 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have been focused on the manufacturing of CNT-reinforced titanium-based composites [13,28,29,30], but fewer studies and experiments have been conducted on the mechanical properties and microstructure of TMCs reinforced with graphene. Cao et al [31] fabricated titanium (Ti–6Al–4V)/graphene nanoflake (GNF) composites via hot isostatic pressing (HIP) followed by isothermal forging and reported that both the yield and ultimate tensile strengths were increased with the addition of GNFs to the matrix, without the loss of ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Tradition flake graphite (FG) (a major carbon source for carbon-containing refractories) does not meet the requirements of advanced steelmaking technology and low-carbon carbon-containing refractories (LCCRs). Moreover, researchers have devoted a lot of effort to developing LCCRs by adding nano-sized carbon sources [7,8,9]. First, carbon black (CB), as a zero-dimensional nano-sized carbon source, replaced FG partially or entirely.…”
Section: Introductionmentioning
confidence: 99%